Cam Jansen and the mystery at the haunted house - Adler, David A.; Natti, Susanna (New York, N.Y. : Viking, 1992)
Cam and her friend Eric chase the thief of Aunt Katie's wallet through an amusement park and find themselves involved in another case requiring their special detective skills.
Book Links (A.L.A.).
School Library Journal.
Wilson's Children.
3.2
3-6
Keywords: Mystery and detective stories; Mystery fiction